Integration of tactical aspects into strategic production network planning - Auberger, Elias (Array, 2020)
Nowadays, production companies are facing an increasingly volatile environment. Due to increasing globalization, but also de-globalization, taking into consideration an internal production network is becoming more and more important for companies, all in order to be able to counteract in an agile way the uncertainties such as swings in the demand. Current production network planning procedures focus on (re-)locating decisions without delving into what happens inside the plants, neglecting the dynamics of production networks, following a rigid top-down approach during the configuration phase, and they do not integrate the effects of planning tasks at the factory level (tactical and operational planning). In order to be able to make strategic decisions with a well-founded database regarding the production network, the effects on the tactical and operational level must be considered in an iterative way during the strategic decision-making process. The aim of this research is to define the requirements for an approach to strategic production network planning, which considers the effects at the tactical and operational level in an iterative way, and to develop a process model, derived from the requirements, that in its five phases considers the deficiencies of the existing approaches.